ANALISIS FAKTOR DETERMINAN KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS PAAL V KOTA JAMBI - Ulfayul Septuminza; Fadliyana Ekawaty; Suryati (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
Pneumonia in children under five remains a public health problem in the working area of Paal V Public Health Center, Jambi City. This study aimed to identify the determinants associated with the incidence of pneumonia among children under five. This quantitative study employed a case-control design involving 118 respondents, consisting of 59 cases and 59 controls selected using a purposive sampling technique. Data were analyzed using univariate analysis, bivariate analysis with the Chi-Square test, and multivariate analysis using binary logistic regression. The results showed that low birth weight (LBW) (p=0.001), exclusive breastfeeding (p=0.025), nutritional status (p=0.023), vitamin A supplementation (p=0.004), immunization status (p<0.001), exposure to cigarette smoke (p=0.009), and maternal knowledge level (p<0.001) were significantly associated with the incidence of pneumonia. Multivariate analysis indicated that LBW, immunization status, and maternal knowledge remained significantly associated with pneumonia, with LBW identified as the most dominant factor. It can be concluded that pneumonia prevention among children under five should focus on preventing low birth weight, improving immunization coverage, and enhancing parental health education.